Pengaruh Etika Bisnis Terhadap Pertumbuhan Ekonomi Perdagangan Kecil Sebuah Usaha Sendal Sepatu Dan Tas Di Wilayah Pasar Baru Cikarang Utara - Velintinus Riyan Tamba (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The impact of business ethics on the microeconomic growth of small businesses in the North Cikarang Market has become a major concern in recent years. This study aims to investigate how business principles affect the microeconomic growth of small businesses in the new Cikarang North Market area. The results of the study indicate that business ethics have a significant influence on the economic growth of small businesses in the North Cikarang Market. The business principles applied by entrepreneurs in the area help increase consumer trust, product and service quality, and community participation in economic activities. Therefore, steps are needed to increase awareness of business ethics among entrepreneurs in the North Cikarang Market in order to support the microeconomic growth of small businesses in the area. The purpose of this study was to find and analyze the impact of business ethics on microeconomic growth in small trade in the North Cikarang Market. The research method used was qualitative by conducting interviews with micro business owners in the market on Thursday, April 24, 2025, in the afternoon at 11.00 at the new Cikarang North Market through surveys and interviews. The results of the analysis are expected to provide a deeper understanding of how business ethics practices can influence microeconomic growth in the new market area of North Cikarang.